2018
DOI: 10.15561/18189172.2018.0305
|View full text |Cite
|
Sign up to set email alerts
|

Power abilities: recognition of the level of development in girls aged 12-14 years

Abstract: Purpose:The purpose of the study is to determine the possibility of recognizing the state of power abilities development in girls aged 12-14 years based on the methodology of multidimensional statistics. Material:The study involved girls: 12 (n =21), 13 (n = 20), 14 (n = 19) years old. Conclusions:Discriminant analysis allowed to determine informative indicators for cross-control of the development of power abilities in girls aged 12-14 years; answer the question of how significantly the state of development … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 9 publications
2
5
0
Order By: Relevance
“…The above-mentioned results show that discriminant analysis allows to identify the state of motor abilities development in boys aged 12-14 by the results of testing and supplement data on the use of discriminant function in classifying schoolchildren by motor activity (Gert-Jan de Bruijn, & Benjamin Gardner, 2011; Lulzim, 2013). As in the papers by Broadhead and Church (1982), Ivashchenko, Kapkan, Khudolii, and Yermakova (2017), Ivashchenko, Khudolii, Iermakov, Veremeenko, and Lopatiev (2018), we observed a high discriminative and predictive ability of these functions in evaluating motor preparedness of boys aged 12-14. The study confirmed that multidimensional methods of mathematical statistics such as factor and discriminant analyses (Ivashchenko, 2014;Lopatiev, Ivashchenko, Khudolii, Pjanylo, Chernenko, & Yermakova, 2017;Ivashchenko, Khudolii, Iermakov, Chernenko, & Honcharenko, 2018) are effective for studying the structure of motor preparedness of boys aged 12-14.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The above-mentioned results show that discriminant analysis allows to identify the state of motor abilities development in boys aged 12-14 by the results of testing and supplement data on the use of discriminant function in classifying schoolchildren by motor activity (Gert-Jan de Bruijn, & Benjamin Gardner, 2011; Lulzim, 2013). As in the papers by Broadhead and Church (1982), Ivashchenko, Kapkan, Khudolii, and Yermakova (2017), Ivashchenko, Khudolii, Iermakov, Veremeenko, and Lopatiev (2018), we observed a high discriminative and predictive ability of these functions in evaluating motor preparedness of boys aged 12-14. The study confirmed that multidimensional methods of mathematical statistics such as factor and discriminant analyses (Ivashchenko, 2014;Lopatiev, Ivashchenko, Khudolii, Pjanylo, Chernenko, & Yermakova, 2017;Ivashchenko, Khudolii, Iermakov, Chernenko, & Honcharenko, 2018) are effective for studying the structure of motor preparedness of boys aged 12-14.…”
Section: Discussionsupporting
confidence: 81%
“…The obtained data made it possible to reveal the peculiarities of motor abilities development in boys aged 12-14. While to identify the state of motor abilities development in girls aged 12-14 years, the most important results are obtained in tests characterizing the development level of strength of shoulder and leg muscles; in girls aged 13-14 -the results of tests characterizing the development level of relative and static leg strength (Ivashchenko, Khudolii, Iermakov, Veremeenko, & Lopatiev, 2018), to identify the state of motor abilities development in boys aged 12-14, the most important results are those obtained in tests that characterize the comprehensive development of motor abilities; in boys aged 13-14 -the results of tests that characterize the development level of relative and static leg strength, strength endurance of abdominal muscles, and dynamic strength of shoulder muscles.…”
Section: Discussionmentioning
confidence: 99%
“…The low physical activity level of schoolchildren is the main reason for their health deterioration and requires the development of methodological approaches to physical education in educational institutions (Krutsevych, & Chervotoka, 2019;Bahinska, 2015;Garkusha, 2013). The regulation of physical loads in physical education lessons is one of the factors that ensure the effectiveness of schoolchildren's physical education (Ivashchenko, Khudolii, Iermakov, Veremeenko, & Lopatiev, 2018;Veremeenko, Khudolii, & Ivashchenko, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Technological approaches to the assessment of training effects of strength training loads, pedagogical control of the level of motor fitness in primary school pupils have been studied in a number of works (Ivashchenko, Khudolii, Iermakov, & Harkusha, 2017;Ivashchenko, Khudolii, Iermakov, Chernenko, & Honcharenko, 2018;Ivashchenko, 2016). One of the technological approaches is the use of pattern recognition methods (Neimark, & Teklina, 2007Ivashchenko, Khudolii, Iermakov, Veremeenko, & Lopatiev, 2018). In research on the effectiveness of strength development, there is an issue of studying single-factor and multi-factor impacts on the formation of immediate and delayed training effects.…”
Section: Introductionmentioning
confidence: 99%
“…This leads to certain differences in the methodology of teaching a particular sport. Physical training in gymnastics solves problems of development and maintenance of high level of motor qualities -flexibility, coordination abilities, speed, strength, speed-power qualities, their combined improvement with the technique of exercises and the ability to manifest these physical qualities in conditions of competitive activity activities (Ivashchenko, Khudolii, Iermakov, Bartik, & Prykhodko, 2018;Ivashchenko, Khudolii, Iermakov, Veremeenko, & Lopatiev, 2018;Huzar, Shalar, & Savchenko-Marushchak, 2016). The highest rates of volume and intensity of physical training exercises are observed in the development phase.…”
Section: Introductionmentioning
confidence: 99%